1992
DOI: 10.1055/s-2007-1006729
|View full text |Cite
|
Sign up to set email alerts
|

Successful Replantation of the Lower Leg after 42-Hour Ischemia: Case Report

Abstract: A case of right lower-leg replantation after 42-hr ischemia is presented. Revascularization of the other foot with circulatory decompensation after 36-hr ischemia was carried out simultaneously. The replanted lower leg survived. Following its shortening in replantation by 12 cm, right lower-leg lengthening by 8 cm was carried out 1.5 years after replantation with the aid of a distraction apparatus. The locomotor function in both lower extremities recovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Successful replantation of the lower leg after 42-hour ischemia has been reported. 8 However, one thing is obvious: the longer the ischemia time, the worse the prognosis of replantation in terms of both survival and functional outcome. Cooling of the amputated segment alleviates the unfavorable effects of ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful replantation of the lower leg after 42-hour ischemia has been reported. 8 However, one thing is obvious: the longer the ischemia time, the worse the prognosis of replantation in terms of both survival and functional outcome. Cooling of the amputated segment alleviates the unfavorable effects of ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…That is why many surgeons were rather skeptical about lower-limb replantations and did not consider them indicated. [1][2][3] Although cases of lower-extremity replantations have been reported, [4][5][6][7][8] there is a deficiency in the analysis of long-term results in the literature. Cases of simultaneous replantation of both lower legs are extremely rare, and only a few such cases have been reported in the literature.…”
mentioning
confidence: 99%
“…7 (2) Due to extensive blood loss, the general conditions are often too serious to perform replantation surgery. 8,9 (3) Long ischemia time affecting the muscles increases the risk of severe complications, such as replantation toxemia, sepsis, myoglobinuria, and renal shutdown. [8][9][10][11][12] (4) Motor and sensory functions in the ankle and toes are usually poor.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, Vasconez and Nocholls, 16 in their review article, introduced the above treatment as an option for severe open injuries, recommending this method because of both simplicity and facilitation of vascular, neural, and soft-tissue repair. Several authors [17][18][19]22 reported that complete or partial amputation of the lower limb could be successfully managed by primary shortening with secondary limb lengthening. Other surgeons 21,25 also treated severe open tibial fractures by this method combined with local or free flaps.…”
Section: (A) Radiograph On the Original Injury (B) Radiologic Appementioning
confidence: 99%
“…13,14 Moreover, the application of primary shortening with secondary limb lengthening for severe open fractures, as a modification of the above procedures, has been reported by many authors. [15][16][17][18][19][20][21][22][23][24][25][26][27] However, few articles describing the longterm outcome of severe open fractures treated with this treatment have been published, to our knowledge.…”
mentioning
confidence: 99%